2022
DOI: 10.12968/bjom.2022.30.1.10
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of the media's influence on UK women's views of breastfeeding

Abstract: Background In the UK, rates of exclusive breastfeeding at 6 months are at 1%, highlighting the need to encourage and improve the support provided to women to initiate and continue breastfeeding and to improve infant and maternal health. This study aimed to qualitatively explore the influence of media on the intention to initiate and continue breastfeeding. Methods This ethnographic study recruited 40 women; 31 with children and nine of childbearing age (19–28 years), with the intention to have children. Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…While it is important to promote the benefits of exclusive breastfeeding (Couto et al 2020), it is important that this is done in a cautious and compassionate way that provides information and support to mothers without judgement. The findings from this study, and others suggest that while well-intentioned, campaigns such as 'Breast is Best' may not be promoting breastfeeding in the positive and inclusive way that is needed by mothers (Keevash et al 2018, Srivastava et al 2022. Instead, encouraging breastfeeding alongside honesty about the difficulties inherent with breastfeeding and compassion for those who struggle may prove more effective (Keevash et al 2018).…”
Section: Implications For Practice and Policymentioning
confidence: 59%
See 1 more Smart Citation
“…While it is important to promote the benefits of exclusive breastfeeding (Couto et al 2020), it is important that this is done in a cautious and compassionate way that provides information and support to mothers without judgement. The findings from this study, and others suggest that while well-intentioned, campaigns such as 'Breast is Best' may not be promoting breastfeeding in the positive and inclusive way that is needed by mothers (Keevash et al 2018, Srivastava et al 2022. Instead, encouraging breastfeeding alongside honesty about the difficulties inherent with breastfeeding and compassion for those who struggle may prove more effective (Keevash et al 2018).…”
Section: Implications For Practice and Policymentioning
confidence: 59%
“…Additionally, midwifery and health visiting services throughout the UK need to provide more tailored support and information to mothers attempting to initiate and continue breastfeeding (Norman et al 2022;Srivastava et al 2022;Keevash et al 2018). It is also imperative that services provide better mental health support to mothers who are experiencing either pre-morbid mental health issues, or who start to develop difficulties as a result of breastfeeding.…”
Section: Implications For Practice and Policymentioning
confidence: 99%
“…The powerful sociocultural impact of media is well-established; it has the potential to both positively (Nwachukwu and Anorue, 2019; Dunn, 2020) and negatively (Srivastava et al , 2022; Turner & Lefevre, 2017) influence the general public about a wide range of topics. Owing to the general public’s familiarity with media, media-based interventions are commonly used as education strategies (Garcia, 2022; Goodwin et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Iceland is one of the countries with the highest breastfeeding rates, with 74% of women still breastfeeding at 6 months after giving birth and 27% at 1 year after giving birth (Símonardóttir, 2016 ). By contrast, the United Kingdom has one of the lowest figures in the world, the latest countrywide survey in 2010 revealed that only 1% of babies were exclusively breastfed at 6 months (Srivastava et al, 2020 ). Although there is no up-to-date figure about this period, a recent survey showed that just 48% of British women continue breastfeeding beyond 6–8 weeks (UKHSA, 2021 ).…”
Section: Introductionmentioning
confidence: 99%